The effec of shoots of Allium sativum L., Ferula assa-foetida aqueous extract and low frequency electromagnetic field on angiogenesis in chick chorioallantoic membrane (in vivo) - SD Sadoughi; S Zafar-Balanjad; J Baharara; KH Nejhad Shahrokhabadi; H Sepehri Moghadam; R Rahbarian (Institue of Medicinal Plants, ACECR, 2015)
Background: Angiogenesis in cancer tissue leads to development of cancer and inhibition of angiogenesis is one of the goals of cancer treatment. In traditional medicine, Allium sativum L. and Ferula assa-foetida are considered as the most important medicinal plants. In addition, the effect of electromagnetic field on the cell growth in different aspects has been confirmed. Objective: This study was conducted to investigate the effect of shoots of Allium sativum L., Ferula assa-foetida extract and low frequency electromagnetic field on angiogenesis. Methods: Hundred Hyline fertilized eggs were randomly divided into ten groups: the control (treated with distilled water), sham one (treated with normal saline), sham two (treated with electromagnetic field off), experimental one (treated with shoot of Allium sativum L. extract), experimental two (treated with shoot of Ferula assa-foetida extract), experimental three (treated with combination of Allium sativum L. and Ferula assa-foetida extract), experimental four (Treated with electromagnetic field with intensity of 100 gauss), experimental five (Treated with Allium sativum L. extract + electromagnetic field), experimental six (Treated with Ferula assa-foetida extract + electromagnetic field), experimental seven (Treated with combination of Allium sativum L. and Ferula assa-foetida extract + electromagnetic field). The extract was injected on the eighth day of incubation and treated with electromagnetic field radiation was done on the tenth day. On the twelfth day, Chorioalantoic membrane of samples photographed then the length and numbers of vessels was measured. Results: The mean number and length of blood vessels in experimental groups one, two, four, five and six were significantly decreased compared to the control. The most significant decrease of mean number and length of blood vessels was created in group three, especially in group seven (p>0.05). In addition, extract of Ferula assa-foetida has anti-angiogenesis effect more than Allium sativum L. Conclusion: Shoot of Allium sativum L. and Ferula assa-foetida extract have inhibitory effects on angiogenesis and these effects amplifying by electromagnetic field.